The effectiveness of entrepreneurship workshop programs in higher education on improving students' soft skills: systematic literature review - Hidayah, Nur; Sulisworo , Dwi; Widodo, Hendro (Universitas Ahmad Dahlan, 2024)
This systematic literature review examines review focuses on a particular type of entrepreneurship program entrepreneurship programs' effectiveness in improving students' soft skills in higher education. Through analysis of 25 research articles from Scopus-indexed journals published between 2018-2024, this study investigates the effectiveness, influencing factors, and challenges in implementing entrepreneurship programs. The findings reveal that entrepreneurship programs demonstrate varying degrees of success in developing students' soft skills, with effectiveness heavily influenced by implementation methods and learning contexts. Factors affecting program success include curriculum design, teaching methods, instructor quality, and industry integration. Common challenges include limited funding, insufficient qualified instructors, and gaps between academic content and industry needs. The review suggests that successful implementation requires a holistic approach integrating adaptive curriculum development, instructor capacity building, industry collaboration, and innovative teaching methods. This study contributes to understanding how higher education institutions can design and implement more effective entrepreneurship programs that develop relevant soft skills for contemporary workforce demands. The implication of this research lies in strengthening the capacity building of teachers and learning infrastructure.